Mobile DevOps in Education: Practical Training through Application Development - Luchkevych, Mykhailo; Luchkevych, Viktoriia; Shakleina, Iryna (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This paper investigates the effectiveness of teaching DevOps concepts to students through practical mobile application development. We pay particular attention to the challenges specific to the mobile environment. These include the complexity of deploying applications in stores such as Google Play and the App Store and the need to ensure constant and convenient interaction with mobile users. The paper presents a pedagogical model combining project-based learning, containerization, automated CI/CD processes, and cloud platforms. We adapted these elements to the specifics of mobile development. The research presents examples of student projects that implement DevOps practices. In particular, it describes the automation of testing on different types of mobile devices, the setup of build and deployment processes, and the monitoring of application performance in a cloud environment. This study conducts a comparative analysis between the traditional approach to training and the DevOps-oriented methodology. The indicators considered include update cycle duration, number of errors, and adaptation to mobile platforms. The results confirmed that using DevOps in mobile development education improves the quality of students’ technical training, promotes the development of their practical skills, and enhances their competitiveness in the field of mobile technologies.